1980
DOI: 10.1073/pnas.77.10.5812
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-regulated phosphorylation in synaptosomal cytosol: dependence on calmodulin.

Abstract: Calcium stimulated the phosphorylation of several specific synaptosomal cytosolic proteins. The effects of calcium were both concentration and time dependent and were most apparent for proteins with molecular weights of 50,000, 55,000, and 60,000. Exogenous calcium (1.0-100 ,M) enhanced the net incorporation of phosphate into protein by as much as 23-fold. In (5), and synaptosomal lysates (6). Evidence indicates that the calcium-dependent phosphorylation of synaptic plasma membranes (2) and synaptic vesicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Both Ca2" and cAMP can affect the integrity of cytoskeletal components and these alterations may provide a mechanism for regulating secretory processes in the cell (4,14,16). In several cell systems, studies have suggested that Ca2+-dependent phosphorylation plays a role in secretory process (4,9,(45)(46)(47). In Sertoli cells both Ca2+ (17,18) and cAMP (17)(18)(19) have been implicated in mediating follicle-stimulating hormone-induced responses and some of these effects may occur by rearrangement of the cytoskeleton.…”
mentioning
confidence: 99%
“…Both Ca2" and cAMP can affect the integrity of cytoskeletal components and these alterations may provide a mechanism for regulating secretory processes in the cell (4,14,16). In several cell systems, studies have suggested that Ca2+-dependent phosphorylation plays a role in secretory process (4,9,(45)(46)(47). In Sertoli cells both Ca2+ (17,18) and cAMP (17)(18)(19) have been implicated in mediating follicle-stimulating hormone-induced responses and some of these effects may occur by rearrangement of the cytoskeleton.…”
mentioning
confidence: 99%
“…Protein phosphorylation accompanies exocytotic activity in endocrine (1,7,8,16,37) and exocrine (3,9,27,36) gland cells as well as in mast (39,41) and nerve (11,23,25) cells. Whereas a dephosphorylation of single proteins was reported to occur only rarely during stimulation (3,9,40), in a comparison of different systems the opposite was observed quite frequently with a considerable number of proteins, which were all of different molecular weights.…”
mentioning
confidence: 99%
“…We will refer to it as synapsin I kinase to distinguish it from other calmodulin-dependent protein kinases. It is found in both soluble and particulate fractions of brain homogenates (37) (34,(37)(38)(39), where they account for a major portion of the endogenous "substrates" for calmodulin-dependent protein kinase in the 50-to 60-kDa region of NaDodSO4/polyacrylamide gels (37).…”
mentioning
confidence: 99%
“…We have recently purified and characterized a brain calmodulin-dependent protein kinase (34) (34,(37)(38)(39), where they account for a major portion of the endogenous "substrates" for calmodulin-dependent protein kinase in the 50-to 60-kDa region of NaDodSO4/polyacrylamide gels (37).…”
mentioning
confidence: 99%